A comprehensive understanding of water photooxidation on Ag3PO4 surfaces. Issue 39 (3rd May 2017) - Ma, Zuju; Lin, Sen; Sa, Rongjian; Li, Qiaohong; Wu, Kechen
Abstract : A systematic study of the mechanism of OER on Ag3 PO4 surfaces by combining hybrid DFT calculations and first principles thermodynamics. Abstract : The oxygen evolution reaction (OER) is known to be the bottleneck of water-splitting. Ag3 PO4 is a highly efficient visible light photocatalyst for dye degradation and water oxidation to O2, with a higher OER rate than BiVO4 and WO3 . Despite extensive studies on Ag3 PO4, the surface properties including surface electronic states, reaction sites and mechanisms of OER on Ag3 PO4 surfaces are not clear at present. Herein, we reported a comparative first-principles density functional theory study of the bulk, surface properties and the mechanism of OER on the three primary low index facets of Ag3 PO4 : (100), (110) and (111). We revealed for the first time that the rate-limiting step of the OER on Ag3 PO4 (100), (110) and (111) surfaces is the dehydrogenation of HO* (HO* → O* + H + + e − ), which is different from most reported metal oxides and nitrides like TiO2 and g-C3 N4 . The OER process on the (100) surface tends to proceed by following a different mechanism as that on the (110) and (111) surfaces. The illumination of the Ag3 PO4 (100), (110), and (111) surfaces with solar light provides enough overpotential for the OER to proceed spontaneously. In particular, the free energy change of removal of the first proton from water on the Ag3 PO4 (111) surface is much lower than that on (100) and (110) surfaces, giving an explanation for the experimentally observed higher catalytic activity of the (111) surface. The exposed phosphorus atoms on the Ag3 PO4 (111) surface promote the dehydrogenation of H2 O and suppress the formation of mid-gap states. Our results are profound for understanding the underlying mechanism of the photocatalytic water oxidation process occurring on Ag3 PO4 surfaces, and serve as a foundation for developing new high-performance Ag3 PO4 based photocatalysts for water splitting and organic contaminant decomposition.